Glucose transporter 1 is important for the glycolytic metabolism of human endometrial stromal cells in hypoxic environment. Issue 6 (June 2020) - Kido, Takeharu; Murata, Hiromi; Nishigaki, Akemi; Tsubokura, Hiroaki; Komiya, Shinnosuke; Kida, Naoko; Kakita-Kobayashi, Maiko; Hisamatsu, Yoji; Tsuzuki, Tomoko; Hashimoto, Yoshiko; Okada, Hidetaka
Abstract: Aim: The study aimed to elucidate the glycolytic metabolism of human endometrial stromal cells (hESCs) in hypoxic environment. Main methods: The hESCs were cultured in hypoxic environment, and their metabolic pathways were analyzed using metabolomics. We assessed glucose uptake using 2-deoxyglucose (2-DG) assay. The expression of glucose transporters (GLUTs) required for glucose uptake was determined using real-time quantitative polymerase chain reaction (qPCR) and western blotting. Furthermore, we knocked down GLUT1 and examined the uptake of 2-DG. Key findings: Under hypoxia, glucose-6-phosphate, fructose-6-phosphate, and fructose-1, 6-diphosphate were significantly elevated in hESCs (P < 0.05). This finding indicated enhancement in glycolysis. The volume of glucose uptake increased significantly under hypoxia (P < 0.05). Hypoxia simultaneously induced the expression of GLUT1 and GLUT3 mRNA (P < 0.05) and attenuated the expression of GLUT8 (P < 0.05). Glucose uptake was significantly inhibited upon knockdown of GLUT1 (P < 0.0001). Significance: These results demonstrated a very important role of glucose transport under hypoxia. Also, hESCs utilize glycolysis to adapt to hypoxic conditions that could occur in menstrual and implantation period. These findings pave the way to study implantation failure and tumors originating from the endometrium. Abstract : Cell biology; Biological sciences; Molecular biology; Cell Culture; Metabolomics; Oxidative Stress; Reproductive System; Women's Health; endometrium; hypoxia; glycolysis; glucose transporter; human endometrial stromal cells